Pengembangan Mobile Learning Berbasis Android untuk Praktikum Aplikasi Transistor - Sumarsono, Widiyandoko; Sugiyanto, Sugiyanto (UPEJ Unnes Physics Education Journal, 2019)
Mobile Learning is a learning model that utilizes information and communication technology. This study aims to produce mobile learning applications and determine the appropriateness of Android-based mobile learning applications on the Transistor Application material that has been developed. This research was classified as research development or research and development. The development model used in this study was ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Futhermore, the application result product directly tested on 2 groups of respondents, namely expert respondents and non-expert respondents. Expert respondents were consisted of both media and material expert. Non-expert respondents were students of the Physics Department who took the Analog Electronics course in semester 2018/2019. The feasibility used in this media was based on Wahono (2006) which consists of software engineering aspects, aspects of learning design, and aspects of visual communication. From the results of the feasibility test in a whole learning media, a percentage value of 91% was obtained. Based on these results, this learning media is very well used as a learning supplement in the practice of transistor application.